2019
DOI: 10.1111/liv.14167
|View full text |Cite
|
Sign up to set email alerts
|

Serum coding and non‐coding RNAs as biomarkers of NAFLD and fibrosis severity

Abstract: Background & Aims In patients with non‐alcoholic fatty liver disease (NAFLD), liver biopsy is the gold standard to detect non‐alcoholic steatohepatitis (NASH) and stage liver fibrosis. We aimed to identify differentially expressed mRNAs and non‐coding RNAs in serum samples of biopsy‐diagnosed mild and severe NAFLD patients with respect to controls and to each other. Methods We first performed a whole transcriptome analysis through microarray (n = 12: four Control: CTRL; four mild NAFLD: NAS ≤ 4 F0; four severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 46 publications
(103 reference statements)
0
53
0
1
Order By: Relevance
“…Recent in vitro studies reported aberrant expression of lncRNA during HSC activation, and this was confirmed in two in vivo studies examining liver tissue of NAFLD and NASH patients [79][80][81]. In biopsy-proven NAFLD patients with disease of different severity, another small study showed difference in the expression profile of patients when compared to normal liver [82].…”
Section: Emerging Circulating Biomarkersmentioning
confidence: 72%
See 1 more Smart Citation
“…Recent in vitro studies reported aberrant expression of lncRNA during HSC activation, and this was confirmed in two in vivo studies examining liver tissue of NAFLD and NASH patients [79][80][81]. In biopsy-proven NAFLD patients with disease of different severity, another small study showed difference in the expression profile of patients when compared to normal liver [82].…”
Section: Emerging Circulating Biomarkersmentioning
confidence: 72%
“…Using immunoprecipitation, it was shown that, in NASH, the low intrahepatic levels of miR-122, rather than a real downregulation, may be a consequence of the increased rate of release into the circulation [84]. It can be hypothesized that hepatocyte-derived exosomes mediate miR-122 sensitization of macrophages to inflammatory signals [82]. Other miR such as miR-34a concentrations were significantly higher in NAFLD patients [85].…”
Section: Emerging Circulating Biomarkersmentioning
confidence: 99%
“…Briefly, 10 ng of total RNA were retrotranscribed in single-stranded cDNA containing T7 promoter sequence at the 5′ end. 3′ Double-stranded cDNA was synthesized by adding an adaptor as a template; pre-IVT amplification reaction was optimized with 12 cycles of amplification, as previously reported [ 59 ]. The double-stranded DNA was used as a template for antisense RNA synthesis and overnight amplification (14 h) by in vitro transcription (IVT), using T7 RNA polymerase.…”
Section: Methodsmentioning
confidence: 99%
“…Palmitate solution (Sigma-Aldrich, Saint Louis, MO, USA) was prepared as previously reported [ 30 ] and was diluted in culture medium. DCI was kindly provided by Amicogen Inc. (Jinju, Korea) and shipped by Vivatis Pharma GmbH (Hamburg, Germany).…”
Section: Methodsmentioning
confidence: 99%